Outcomes of interfacility helicopter transportation in acute stroke care. Issue 5 (October 2020) - Almallouhi, Eyad; Al Kasab, Sami; Nahhas, Michael; Harvey, Jillian B.; Caudill, Juanita; Turner, Nancy; Debenham, Ellen; Giurgiutiu, Dan-Victor; Leira, Enrique C.; Switzer, Jeffrey A.; Holmstedt, Christine A.
Abstract : Objective: To evaluate the long-term functional outcome of interhospital transfer of patients with stroke with suspected large vessel occlusion (LVO) using Helicopter Emergency Medical Services (HEMS). Methods: Records of consecutive patients evaluated through 2 telestroke networks and transferred to thrombectomy-capable stroke centers between March 2017 and March 2018 were reviewed. Inverse probability of treatment weighting (IPTW) using the propensity score was performed to address confounding factors. Multivariate logistic regression analysis with IPTW was used to determine whether HEMS were associated with good long-term functional outcome (modified Rankin scale score ⩽ 2). Results: A total of 199 patients were included; median age was 67 years (interquartile range [IQR] 55–79 years), 90 (45.2%) were female, 120 (60.3%) were white, and 100 (50.3%) were transferred by HEMS. No significant differences between the 2 groups were found in mean age, sex, race, IV tissue plasminogen activator (tPA) receipt, and thrombectomy receipt. The median baseline NIH Stroke Scale score was 14 (IQR 9–18) in the helicopter group vs 11 (IQR 6–18) for patients transferred by ground ( p = 0.039). The median transportation time was 60 minutes (IQR 49–70 minutes) by HEMS and 84 minutes (IQR 25–102 minutes) by ground ( p < 0.001). After weighting baseline characteristics, the use of HEMS was associated with higher odds of good long-term outcome (OR 4.738, 95% CI 2.15–10.444, p < 0.001) controlling for transportation time, door-in-door-out time, and thrombectomy and tPA receipt. The magnitude of the HEMS effect was larger in thrombectomy patients who had successful recanalization (OR 1.758, 95% CI 1.178–2.512, p = 0.027). Conclusions: HEMS use was associated with better long-term functional outcome in patients with suspected LVO, independently of transportation time.